Mensuração da carga de trabalho de enfermeiros em central de quimioterapia - Souza, Célia Alves de (2012)
The increasing of attendances in the Chemotherapy Center has demanded from the nurses a better standard of time management and productivity. Considering this, the measurement of the work load becomes fundamental. This investigation, which is based on observation, has used the sample work technique and it presents the following aims: 1- identifying and validating the activities developed by nurses in a Chemotherapy Center and; 2- to measure the work load and productivity. The stage is a Chemotherapy Central placed in the South-East of Brazil. Nine assistant nurses have taken part (moments 1 and 2) and other seven of them (moments 3 and 4) during the period from May, 2010 to March, 2011. The study has been conducted in four moments: 1- identification of the interventions/activities, 2- validation of content, 3. pilot test and, 4- measuring of work load. In order to identify the activities performed by the nurses, a device was built using triangulation of data, combining three sources of information: semi-structured interview, documents analysis and questionnaire. The activities mapped have been categorized according to the language patterned by the Nurse Intervention Classification (NIC). Afterwards, the device has been submitted to content validation through meetings with the members. The final instrument was formed by 35 interventions and 48 activities organized in five areas (basic physiologic and complex physiologic, behaviorist, security and health system) and 11 classes. The pilot test using the instrument, conducted by two nurses during four consecutive days, has totaled 1000 samples and has resulted in 38 interventions and 88 activities. The sample size has been statistically established. The observations have been conducted during five days totalizing 1.487 samples of interventions/activities. It has been observed that 43,2% of the nurses time have been spent in indirect care, 33,2% indirect care, 11,6% in associated activities and 12% in personal activities. The average productivity has corresponded to 88%. This study has allowed the mapping and the validation of interventions/activities conducted during the attendance process. There has been concluded that nurses from the investigated unit have spent most of their time performing activities of indirect care. It has highlighted, furthermore, productivity indexes above the recommended ones present in the literature.